Implementation of Buck-Boost Converter with Coupled Inductor for Photo-Voltaic System - M.S. Subbulakshmi; D. Vanitha (Bulletin of Electrical Engineering and Informatics, 2014)
The solar energy is a very interesting alternative on supplement the electrical system generation. In this paper, a photovoltaic based system is obtained from a boost cascaded with a buck converter along with Coupled inductor. Due to its novel operating modes, high efficiency can be achieved because there is only one switch operating at high frequency at a time, and the converter allows the use of power MOSFET and ultra-fast reverse recovery diode. This paper begins with theoretical analysis and modeling of this boost–buck converter. The model indicates that the coupled inductance will lead to an increase in the gain and the decrease in ripples. Finally, this paper analyzes and describes step by step the process of designing, and simulation of high efficiency low ripple voltage buck boost DC-DC converter for the photovoltaic solar conversion system